2021
DOI: 10.1093/nar/gkab1167
|View full text |Cite
|
Sign up to set email alerts
|

DNA methylation variation along the cancer epigenome and the identification of novel epigenetic driver events

Abstract: While large-scale studies applying various statistical approaches have identified hundreds of mutated driver genes across various cancer types, the contribution of epigenetic changes to cancer remains more enigmatic. This is partly due to the fact that certain regions of the cancer genome, due to their genomic and epigenomic properties, are more prone to dysregulated DNA methylation than others. Thus, it has been difficult to distinguish which promoter methylation changes are really driving carcinogenesis from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 68 publications
0
5
0
Order By: Relevance
“…Growing evidence showed that aberrant methylation was associated with oncogenesis and may have a significant clinical value [ 22 ]. Therefore, we assessed the DNA methylation levels of SETDB1 and its prognosis value in various human cancers.…”
Section: Resultsmentioning
confidence: 99%
“…Growing evidence showed that aberrant methylation was associated with oncogenesis and may have a significant clinical value [ 22 ]. Therefore, we assessed the DNA methylation levels of SETDB1 and its prognosis value in various human cancers.…”
Section: Resultsmentioning
confidence: 99%
“…Promoter-level methylation measurements calculated from probe-level methylation data in TCGA were used in this analysis ( Heery and Schaefer, 2021 ). For each gene, the most upstream promoter was considered for the analysis.…”
Section: Methodsmentioning
confidence: 99%
“…For instance, Søes et al found promoter hypomethylation and increased expression of putative OCG ELMO3 to be associated with development of non-small cell lung cancer [20]. Other studies have also identified driver genes with aberrant methylation profiles [21][22][23][24][25][26][27][28]. For example, one study identified 118 differentially expressed methylation-driven genes associated with lung adenocarcinoma of which five genes (CCDC181, PLAU, S1PR1, ELF3, KLHDC9) were used to construct a prognostic risk model which could divide patients with lung adenocarcinoma into high-and low-risk groups [28].…”
Section: Introductionmentioning
confidence: 99%